The Characteristics and Experiences of Canadian Students Receiving Special Education Services for Emotional/Behavioural Difficulties - Beran, Tanya (2009)
This paper provides a description of the demographic characteristics as well as the social and academic experiences of a nationally representative sample of Canadian students receiving special education services for an Emo-tional/Behavioural Difficulty (EBD) and a comparison group of students without disabilities (ND). Data summarized in this article were drawn from the National Longitudinal Survey of Children and Youth. Results reveal numerous areas of dif-ference between groups from student, parent, and teacher perspectives. In particular, the EBD group contained a significantly greater proportion of boys and students from low income families. Students in the EBD group reported hav-ing difficulty making friends and not liking school as much as their ND peers. Academic expectations reported by teachers and parents for children with EBD were significantly lower than for children without disabilities. Discussions of these findings as well as implications for practice and for future research are pre-sented